2022
DOI: 10.1049/nbt2.12075
|View full text |Cite
|
Sign up to set email alerts
|

Hypnea musciformis ‐mediated Ag/AgCl‐NPs inhibit pathogenic bacteria, HCT‐116 and MCF‐7 cells’ growth in vitro and Ehrlich ascites carcinoma cells in vivo in mice

Abstract: In the present study, Ag/AgCl-NPs were biosynthesised using Hypnea musciformis seaweed extract; NPs synthesis was confirmed by a change of colour and observation of a razor-sharp peak at 424 nm by UV-visible spectroscopy. Synthesised nanoparticles were characterised by transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray powder diffraction and Fourier transform infrared spectroscopy. Bacterial cell growth inhibition proves that the Ag/AgCl-NPs have strong antibacterial activity and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Several cases of successful use of silver nanoparticles (AgNPs) for the inhibition of the growth of Ehrlich ascites in vivo and several cancer cell lines in cell cultures have been reported [44][45][46][47][48]. There is no universally accepted concept that would explain the action of AgNPs up to date.…”
Section: Introductionmentioning
confidence: 99%
“…Several cases of successful use of silver nanoparticles (AgNPs) for the inhibition of the growth of Ehrlich ascites in vivo and several cancer cell lines in cell cultures have been reported [44][45][46][47][48]. There is no universally accepted concept that would explain the action of AgNPs up to date.…”
Section: Introductionmentioning
confidence: 99%
“…Although HME-induced significant apoptosis in both cancer cell lines, apoptotic cells were not the majority of total cells at any time point of treatment, suggesting that HME may induce cancer cell death through apoptosis along with other programmed cell death forms (e.g., ferroptosis, necroptosis and pyroptosis) or autophagy. Interestingly, Ghose et al, have recently shown that H. musciformis extract inhibited MCF-7 breast cancer cell growth through autophagy besides apoptosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since NF-κB antagonizes p53 [ 74 ], its inhibition by the upregulated NFKBIA would further enhance our observed p53 signature in HepG2 cells. Interestingly, NF-κB was not responsible for H. musciformis extract-induced apoptosis in MCF-7 breast cancer cells [ 12 ]. Nevertheless, other seaweed extracts have also been reported to regulate cancer progression through attenuation of the p53-NF-kB antagonistic axis [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations